Cascade Reaction by Chemo‐ and Biocatalytic Approaches to Obtain Chiral Hydroxy Ketones and anti 1, 3‐Diols. Issue 5 (25th May 2018) - Gandolfi, Raffaella; Facchetti, Giorgio; Christodoulou, Michael S.; Fusè, Marco; Meneghetti, Fiorella; Rimoldi, Isabella
Abstract: A chemo‐ and biocatalytic cascade approach was applied for the stereoselective synthesis of hydroxy ketones and the corresponding 1, 3‐diols. A new class of tridentate N, N, O ligands was used with copper(II) complexes for the asymmetric β‐borylation of α, β‐unsaturated compounds. The complex containing ligandL5 emerged as the best performer, and it gave the organoborane derivatives with good ee values. The corresponding keto–alcohol compounds were then bioreduced by yeasts. The biotransformation set up with Rhodotorula rubra allowed ( R )‐keto–alcohols and ( S, S )‐diols to be obtained with up to 99 % ee and up to 99 % de in favor of the anti enantiomers. Abstract : Diol M for Murder : A synthetic approach is reported, combining chemo‐ and biocatalysis, starting with the β‐borylation of enriched keto hydroxy compounds by using copper(II) tripodal complexes. Then, resolution of the products, as chiral pure enantiomers (up to 99 % ee ), is realized by yeasts. Concurrently, the corresponding diols are produced in enantiopure form by bioreduction (up to 99 % ee, up to 99 % de ).